IMPLEMENTING E-DISPOSITION SYSTEMS IN REGIONAL PLANNING AGENCIES: EVOLVING GOVERNANCE - Halid, Maryana; Rachman, Ellys; Katili, Andi Yusuf (Public Policy Journal, 2023)
This study aims to determine the Implementation of the E-Diposition Lettering System atthe Secretariat of the Regional Research and Development Planning Board of GorontaloProvince. the type of research used is descriptive using a qualitative approach method, whichrefers to 3 indicators of focus, namely, indicators of Operator Capability, Information, andnetwork Facilities. The results show that: the Implementation of the Correspondence EDipositionSystem at BAPPPEDA Gorontalo Province has not been effective. this is due to theOppartor's lack of ability to implement the Correspondence E-Diposition System. The lack ofinformation or outreach regarding the importance of the E-Disposition System forcorrespondence and the poor internet network in the office environment can hinder the processof inputting mail data into the E-Disposition application